Penentuan Konsentrasi Susu Skim Terbaik dalam Pengencer Semen Ayam Kampung Berbahan Dasar Ringer Laktat (DETERMINATION OF OPTIMUM SKIM MILK CONCENTRATION IN KAMPUNG CHICKEN’S SEMEN EXTENDER BASED ON LACTATED RINGERS) - Khaeruddin Khaeruddin; Andi Nurlinda; Abdul Hakim Fattah; Andi Kurnia Armayanti (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2020)
The aim of this study was to determine the best concentration of skim milk in maintaining the quality of Kampung chicken’s spermatozoa during storage at 5 oC. Semen was collected from five roosters which used massage method. Furthermore, semen was divided into five tubes as treatment (no extenders, extenders containing 0%, 6%, 9% and 12% skim milk concentrations), the liquid semen was stored at 5 oC. Observations of motility, viability and abnormalities of spermatozoa were carried out at 0, 12, 24, 36, dan 48 hours. The results showed that there was a very significant difference (P <0.01) among the treatment of motility, viability and abnormalities of Kampung chicken spermatozoa after dilution during storage. Storage of spermatozoa in 6% skim milk concentrate for 48 hours was resulted in motility of 49,00±1,30%, viability of 52,13±1,53% and abnormalities of 20,47±0,47%. The use of lactated ringer extenders with a concentration of 6% skim milk can generally maintain sperm quality which was better than other treatments during storage.